Development Strategy for Hamadi Beach Tourist Attraction by the Jayapura City Tourism Office - Zulfina Fajriaty; Elsyan R. Marlissa; Halomoan Hutajulu (LPPM STIE KRAKATAU, 2024)
Purpose: This study analyzes the readiness of the four tourism components at Hamadi Beach, evaluates its strategic position through internal and external factor analysis, and formulates sustainable development strategies for the Jayapura City Tourism Office. Methodology: A descriptive qualitative approach was employed, with data collected through observation, interviews, questionnaires, and documentation. The data were analyzed using the Miles and Huberman interactive model and Strengths, Weaknesses,Opportunities, and Threats (SWOT) analysis based on the Internal and External Factor Analysis Summary matrices, while validity was ensured through triangulation. Results: Development remains suboptimal, particularly in facilities and ancillary services, though the destination scores a positive internal difference of 0.10 and a positive external difference of 0.30, placing it in Quadrant I, which calls for an aggressive, growth-oriented strategy. Conclusions: Hamadi Beach possesses strong natural and cultural assets that justify prioritized investment in facility upgrading, digital promotion, community-based cultural tourism, and institutional strengthening. Limitations: The single-site case design and the scoring-based SWOT procedure limit generalization and preclude formal statistical inference. Contributions: The study integrates the 4A tourism framework with a quantified Internal and External Factor Analysis Summary (IFAS-EFAS)-based Strengths, Weaknesses, Opportunities, and Threats (SWOT) analysis in the underexplored context of Hamadi Beach, Papua.